2004
DOI: 10.1161/01.atv.0000118276.87061.00
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative Activity of HDL Particle Subspecies Is Impaired in Hyperalphalipoproteinemia: Relevance of Enzymatic and Physicochemical Properties

Abstract: Objective-Hyperalphalipoproteinemia (HALP) is characterized by elevated plasma levels of high-density lipoprotein (HDL) particles with altered composition, metabolism, and function. The impact of such modification on antioxidative activities of HDL subfractions is indeterminate. Methods and Results-Gradient fractionation revealed that buoyant HDL2b and 2a and small dense HDL3b and 3c levels were elevated up to 2.0-fold in HALP subjects (nϭ9; mean plasma HDL cholesterol, 79 mg/dL) with low hepatic lipase activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
25
0
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(37 citation statements)
references
References 41 publications
9
25
0
3
Order By: Relevance
“…In adults, this association renders HDL proatherogenic, with a loss or reduction of many of its functions, including its reverse cholesterol transport and antioxidant properties (15,(28)(29)(30). Therefore, we suggest that this would also be the case in SAA-enriched HDL from overweight and obese children; in support of this concept, we have shown that the activities of HDL 2 -CETP and HDL 2 -LCAT were also influenced in these overweight and obese cohorts.…”
Section: Discussionsupporting
confidence: 62%
“…In adults, this association renders HDL proatherogenic, with a loss or reduction of many of its functions, including its reverse cholesterol transport and antioxidant properties (15,(28)(29)(30). Therefore, we suggest that this would also be the case in SAA-enriched HDL from overweight and obese children; in support of this concept, we have shown that the activities of HDL 2 -CETP and HDL 2 -LCAT were also influenced in these overweight and obese cohorts.…”
Section: Discussionsupporting
confidence: 62%
“…In this study, plasma TG levels were markedly elevated (ϩ76%) in CHD patients compared with control subjects (Ansell et al, 2003), suggesting that concomitant HDL enrichment in TG might have significantly contributed to the formation of dysfunctional HDL as proposed elsewhere (Hansel et al, 2004;Kontush et al, 2004Kontush et al, , 2005Nobecourt et al, 2005).…”
supporting
confidence: 69%
“…The specific association of the deficient antioxidative activity with small, dense HDL (Hansel et al, 2004;Kontush et al, 2004Kontush et al, , 2005Nobecourt et al, 2005) together with the direct mechanistic link between antiinflammatory and antioxidative activities (Navab et al, 2001a,b) suggests that small, dense HDL is a major subset of the total HDL particle population, which is responsible for both potent anti-inflammatory activity under normal conditions and for deficient activity under pro-atherogenic, pro-inflammatory conditions. This conclusion is consistent with the corrected anti-inflammatory properties of HDL from PLTP-deficient mice, which are characterized by the prevalence of small, lipid-poor HDL particles (Yan et al, 2004).…”
mentioning
confidence: 99%
“…The increase in the unesterifi ed cholesterol content and subsequent increase in esterifi ed cholesterol content within the HDL fraction following CER-001 infusion indicates that the apoA-I within the CER-001 particle is recognized by endogenous LCAT, responsible for cholesterol esterifi cation in plasma ( 27 ). However, the increased HDL-c following CER-001 infusion consisted predominantly of unesterifi ed cholesterol, whereas normally the HDL fraction of cholesterol contains more esterifi ed than unesterifi ed cholesterol ( 28 ). These fi ndings imply suboptimal esterifi cation of the cholesterol mobilized by CER-001.…”
Section: Plasma Lipid Changes Following Cer-001 Infusionmentioning
confidence: 96%